2017
DOI: 10.7554/elife.29292
|View full text |Cite
|
Sign up to set email alerts
|

LRP1 integrates murine macrophage cholesterol homeostasis and inflammatory responses in atherosclerosis

Abstract: Low-density lipoprotein receptor-related protein 1 (LRP1) is a multifunctional cell surface receptor with diverse physiological roles, ranging from cellular uptake of lipoproteins and other cargo by endocytosis to sensor of the extracellular environment and integrator of a wide range of signaling mechanisms. As a chylomicron remnant receptor, LRP1 controls systemic lipid metabolism in concert with the LDL receptor in the liver, whereas in smooth muscle cells (SMC) LRP1 functions as a co-receptor for TGFβ and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 73 publications
4
70
1
Order By: Relevance
“…Indeed, the changes to individual cytokines are comparable in response to the loss of either PI3Kg or LRP1, and both overall result in a pro-inflammatory bias. The equivalent in vivo cytokine responses for PI3Kg and LRP1 KOs have each been published using LPS challenge in PI3Kg À/À mice (Kaneda et al, 2016b) or in two mouse models of macrophage-directed deletion of LRP1 (Mantuano et al, 2016;Xian et al, 2017). In both cases, the findings correlate with our in vitro data showing that loss of PI3Kg or LRP1 produces a similar, pro-inflammatory cytokine bias.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…Indeed, the changes to individual cytokines are comparable in response to the loss of either PI3Kg or LRP1, and both overall result in a pro-inflammatory bias. The equivalent in vivo cytokine responses for PI3Kg and LRP1 KOs have each been published using LPS challenge in PI3Kg À/À mice (Kaneda et al, 2016b) or in two mouse models of macrophage-directed deletion of LRP1 (Mantuano et al, 2016;Xian et al, 2017). In both cases, the findings correlate with our in vitro data showing that loss of PI3Kg or LRP1 produces a similar, pro-inflammatory cytokine bias.…”
supporting
confidence: 82%
“…the phosphorylation of this second tyrosine (Y4507) occurs during atherosclerosis and is required for initiating a signaling cascade along an LRP1/SHC1/PI3K/AKT/ PPARg/LXR axis for cellular cholesterol homeostasis (Xian et al, 2017). Therefore, our reported molecular and functional interaction between the phospho-Y4507 of LRP1 and Rab8 could also provide an underlying molecular link between LRP1 and PI3Kg/Akt during atherosclerosis.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…So the basal levels of LRP1 act as an essential gatekeeper for β cells during DIO. Two recent studies demonstrated LRP1 as a PPARγ coactivator in endothelial cells (45) and in macrophages (46). In contrast, in the context of the β cell, we show here that LRP1 suppresses PPARγ2.…”
Section: Discussioncontrasting
confidence: 36%